Human capital - a pillar of sustainable development. Empirical evidences from the EU states - DIACONU (MAXIM), Laura; POPESCU, Cristian C. (European Journal of Sustainable Development, 2016)
The idea according to which human capital is the main engine of growth has a large support in the specialized literature. In this context, the analysts have argued that sustainable growth and development of a country relies not on a large number of people but on a large amount of human capital. The explanation is simple: a healthier and better educated society involves more productive people, who are able to efficiently evaluate the opportunities and to take the right decisions, a higher social cohesion and more “green skills” that raise the environmental awareness. Considering all these aspects, the main objective of this paper is to identify the way in which human capital, through its qualitative dimensions, influences the sustainable development in the EU states. In order to reach this purpose, we have collected, tabulated and analysed the secondary data offered by various statistical yearbooks, reports and by different empirical investigations. The conclusions of this study may offer valuable information for the EU policy makers regarding the importance of investing in human capital in order to ensure a sustainable development. Keywords: human capital, sustainable development, economic growth, social cohesion, environment protection